"Will it ever be completely safe to be in a crowd again?": the return of disabled supporters to football stadiums during COVID-19. Issue 1 (4th March 2022) - Penfold, Connor; Kitchin, P. J.
ABSTRACT: Our aim in this short article is to provide an analysis of the implications of reopening football stadium doors to a group that have not been at the forefront of management consideration – disabled spectators. In order to achieve this aim, we uphold a social model approach to disability to review the current spectator sport situation across English professional football and outline the problems posed for disabled fans. We then provide the context to disabled people's experiences in football fandom which have often been unsatisfactory. This context then underpins a series of implications that will arise from the reopening of stadia in England. To conclude this commentary, we provide several management recommendations that we argue should facilitate a more disability-inclusive restart for spectator sport.